Refractive Changes after Nd.YAG Laser Capsulotomy in Pseudophakic Patients - Adnan Mahany; Adam Mohamed (AlQalam Journal of Medical and Applied Sciences, 2024)
Postoperative cataract surgery often results in posterior capsule opacification (PCO), causing low visual acuity and uniocular diplopia. Factors include patient age, lens type, surgery technique, and diseases. YAG capsulotomies, a noninvasive procedure, can cause complications like pressure elevation, IOL damage, inflammation, and retinal detachment. The study aims to evaluate the effect of Nd: YAG laser posterior capsulotomy on a patient`s refractive status. This study was conducted at Benghazi Teaching Eye Hospital in Libya. The sample consisted of patients who had anterior capsulorrhexis during cataract surgery and had anterior capsulotomies. Patients were selected based on their condition and underwent a comprehensive eye examination, including refraction, unaided visual acuity, and best-corrected visual acuity. Postoperatively, posterior capsulotomies were performed using a Nd: YAG laser. The surgical techniques involved administering a single shot of Nd: YAG laser, administering topical anesthetic agents, clearing the central posterior capsule, and applying energy levels. The mean age of 63.45 + 7.69 years, with a majority being female (63.6%) and (60.6%) right side eye. The procedure significantly impacted the participants’ visual acuity(P<0.001), with changes in sphere, cylinder, and spherical equivalent measurements (<0.001). A one-month follow-up showed significant improvement in visual acuity, with a trend towards better refractive outcomes. The stability of the cylinder axis suggests a consistent correction of astigmatism post-operatively. The results demonstrate positive long-term outcomes in this study. With the average centroid being 0.52D at 26°±1.31D and 0.65D at 27°±1.23D at one month. The study found that individuals who underwent Nd: YAG posterior capsulotomy had better vision, with refraction changes frequently leading to a hyperopic shift. غالبًا ما تؤدي جراحة إزالة المياه البيضاء بعد العملية الجراحية إلى عتامة المحفظة الخلفية، مما يتسبب في انخفاض حدة البصر وازدواجية الرؤية في عين واحدة. تشمل العوامل عمر المريض، ونوع العدسة وتقنية الجراحة. يمكن أن يسبب شق المحفظة YAG، وهو إجراء غير جراحي، مضاعفات مثل ارتفاع الضغط وتلف عدسة العين الداخلية والالتهاب وانفصال الشبكية. تهدف الدراسة إلى تقييم تأثير شق المحفظة الخلفي بالليزر Nd: YAG على الحالة الانكسارية لعيون المرضى. أجريت هذه الدراسة في مستشفى بنغازي التعليمي للعيون في ليبيا. تكونت العينة من المرضى الذين أصيبوا بالمحفظة الأمامية أثناء جراحة اعتام عدسة العين وأصيبوا بشق المحفظة الأمامية. تم اختيار المرضى بناءً على حالتهم وخضعوا لفحص شامل للعين، بما في ذلك الانكسار، وحدة البصر دون مساعدة، وحدة البصر المصحح. بعد العملية الجراحية، تم إجراء عمليات شق المحفظة الخلفية باستخدام ليزر Nd: YAG. تضمنت التقنيات الجراحية إعطاء ضربة واحدة من ليزر Nd: YAG، باستخدام التخدير الموضعي، وتنظيف الكبسولة الخلفية المركزية، وتطبيق مستويات الطاقة. متوسط العمر 63.45 + 7.69 سنة، غالبيتهم من الإناث (63.6%) و (60.6%) في العين اليمنى. أثر الإجراء بشكل كبير على حدة البصر لدى المشاركين (P <0.001)، مع تغييرات في القياسات الكروية والأسطوانة و المعادلة الكروية (P<0.001). أظهرت المتابعة لمدة شهر تحسنًا ملحوظًا في حدة البصر، مع اتجاه نحو نتائج انكسارية أفضل. يشير استقرار محور الأسطوانة إلى تصحيح ثابت للاستجماتيزم بعد العملية الجراحية. وتظهر نتائج إيجابية على المدى الطويل في هذه الدراسة. مع متوسط النفطة الوسطى هو 0.52D عند 26 درجة ± 1.31D و 0.65D عند 27 درجة ± 1.23D في شهر واحد. وجدت الدراسة أن الأفراد الذين خضعوا لعملية شق المحفظة الخلفية Nd: YAG كانت لديهم رؤية أفضل، مع تغيرات الانكسار التي تؤدي في كثير من الأحيان إلى تحول طول النضر